Water intake, switching between bites and sips, and drinking behavior are associated with food intake across meals varying in spiciness: A secondary analysis of two randomized crossover studies - Paige M. Cunningham; John E. Hayes (Appetite, 2026)

Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Marine heatwaves reorganize phytoplankton bloom phenology in the Gulf of Alaska - Hisatomo Waga; Hiromichi Ueno; Thomas B. Kelly; Curry J. Cunningham; Sarah M. Hendricks (Limnology and Oceanography, 2026)
Phytoplankton blooms structure primary production and food‐web dynamics in the Gulf of Alaska, yet their response to recent warming and marine heatwaves (MHWs) remains poorly described. Using a parametric Gaussian framework applied to 21 years of satellite chlorophyll a (Chl a ), this study classified daily Chl a timeseries into double‐bloom, single spring‐bloom, single fall‐bloom, and no‐bloom regimes and related these to large‐scale oceanographic and atmospheric forcing. Double blooms with distinct spring and fall peaks dominated much of the domain in cold, dynamically active years characterized by negative sea surface temperature anomalies, depressed sea level, strong cross‐shelf pressure gradients, and more frequent storms associated with an intensified Aleutian Low. In contrast, warm years with elevated sea level and weaker cross‐shelf and atmospheric forcing favored single spring blooms and, in some areas, no‐bloom conditions, while single fall blooms occurred under intermediate physical states. Although no significant linear trends in the areal extent occupied by each regime were detected over 2003–2023, years influenced by major MHWs projected strongly onto the warm, weakly forced end of this physical gradient and were associated with reduced double‐bloom extent and an increased prevalence of single spring and no‐bloom regimes. These shifts imply that contraction and weakening of the seasonal production window, with likely consequences for zooplankton growth, match–mismatch dynamics for fish early life stages, and the balance between pelagic retention and export, highlighting how MHWs and ongoing climate change can suppress and reorganize phytoplankton bloom phenology in the Gulf of Alaska.

Increasing the spiciness of a snack slows eating and reduces food and energy intake - Paige M. Cunningham; Eliza Polyak; John E. Hayes (Food Quality and Preference, 2026)

Dangerously ignorant or radically environmentalist? A review and a case study of pollination knowledge systems - Aman Luthra; Ginger RH Allington; Shweta Rana; Renu Suyal; Kiran Cunningham; Ann M. Fraser (Journal of Environmental Studies and Sciences, 2026)

Chemogenetic inhibition of the anterior cingulate cortex increases safe decision-making in aged mice performing the Iowa Gambling Task - Benjamin Z. Roberts; M. Melissa Flesher; Landon F. Cunningham; Adam L. Halberstadt; Jared W. Young (Psychopharmacology, 2026)

Revisiting evolutionary rescue in the wild - Laurinne J. Balstad; Marissa L. Baskett; Stephanie M. Carlson; Curry J. Cunningham; Peter A.H. Westley (Trends in Ecology & Evolution, 2026)

Evaluation of anti-desmoglein-2 antibodies and cardiac biomarkers in Boxer dogs with arrhythmogenic right ventricular cardiomyopathy - L. Dos Santos; S. Cunningham; M. Mantovani (Journal of Veterinary Cardiology, 2026)

A cloud-based JupyterHub platform for community research with the NextGen water resources modeling framework - Ayman Nassar; David G. Tarboton; Furqan Baig; Josh Cunningham; Arpita Patel; James Halgren; Benjamin Lee; Homa Salehabadi; Anthony M. Castronova; Irene Garousi-Nejad (Environmental Modelling & Software, 2026)

Ion chromatography–ultra-high-resolution mass spectrometry reveals EZH2-driven reprogramming of nucleic acid and protein methylation - Mohamed M.Y. Kaddah; Teresa W-M. Fan; Jahid M.M. Islam; Penghui Lin; Teresa A. Cassel; Richard Cunningham; Tom Brown; Richard M. Higashi; Andrew N. Lane (Analytica Chimica Acta, 2026)

Diabetes Nutrition Education and A Food Security Resource for American Indian and Alaska Native Adults With Type 2 Diabetes: A Pilot and Feasibility Randomized Controlled Trial - Sarah A. Stotz; Luciana Hebert; Kelli Begay; Michelle Dennison; Carmen Byker Shanks; Seth A. Berkowitz; Luohua Jiang; Jessica Lafromboise; Nicholas Begick; Barbara Cunningham; Aisa Trice; Danielle Duran; et al. (Journal of Nutrition Education and Behavior, 2026)

Control of fall armyworm with Spodoptera frugiperda multiple nucleopolyhedrovirus in sweet corn cultivated under agroecological conditions - T. Cunningham; C. de la Colina; M. Pérez; G. Quintana; Marco D´Amico; M. Berretta; J. Niz; M. L. Ferrelli; R. Salvador (BioControl, 2026)

Food variety affects food selection and variety-seeking behaviors in an immersive virtual reality food buffet - John W. Long; Paige M. Cunningham; Kathleen L. Keller; Barbara J. Rolls; Travis D. Masterson (Appetite, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Sensory-specific satiety and the influence of variety on snack intake in school-aged children - Paige M. Cunningham; Cara T. Meehan; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2026)

Postnatal environment differentially modulates neurodevelopmental outcomes following voluntary prenatal oxycodone exposure in rats - Kelsea R. Gildawie; Kerri E. Budge; Sara B. Isgate; Jillian Celatka; Megan Gulsby; Cora C. Cunningham; Fair M. Vassoler; Elizabeth M. Byrnes (Neurotoxicology and Teratology, 2026)

Beyond the Surface: Non-Invasive Low-Field NMR Analysis of Microbially-Induced Calcium Carbonate Precipitation in Shale Fractures - Matthew R. Willett; Kayla Bedey; Dustin Crandall; Joseph D. Seymour; Jonny Rutqvist; Alfred B. Cunningham; Adrienne J. Phillips; Catherine M. Kirkland (Rock Mechanics and Rock Engineering, 2026)
Microbially-induced calcium carbonate precipitation (MICP) is a biological process in which microbially-produced urease enzymes convert urea and calcium into solid calcium carbonate (CaCO 3 ) deposits. MICP has been demonstrated to reduce permeability in shale fractures under elevated pressures, raising the possibility of applying this technology to enhance shale reservoir storage safety. For this and other applications to become a reality, non-invasive tools are needed to determine how effectively MICP seals shale fractures at subsurface temperatures. In this study, two different MICP strategies were tested on 2.54 cm diameter and 5.08 cm long shale cores with a single fracture at 60 ℃. Flow-through, pulsed-flow MICP-treatment was repeatedly applied to Marcellus shale fractures with and without sand (“proppant”) until reaching approximately four orders of magnitude reduction in apparent permeability, while a single application of polymer-based “immersion” MICP-treatment was applied to an Eagle Ford shale fracture with proppant. Low-field nuclear magnetic resonance (LF-NMR) and X-Ray computed microtomography (micro-CT) techniques were used to assess the degree of biomineralization. With the flow-through approach, these tools revealed that while CaCO 3 precipitation occurred throughout the fracture, there was preferential precipitation around proppant. Without proppant, the same approach led to premature sealing at the inlet side of the core. In contrast, immersion MICP-treatment sealed off the fracture edges and showed less mineral precipitation overall. This study highlights the use of LF-NMR relaxometry in characterizing fracture sealing and can help guide NMR logging tools in subsurface remediation efforts.

Numerical and experimental investigations into the mechanical behaviour of compacted stranded copper conductors used in dynamic subsea power cables - Dominic M. Smith; Lee S. Cunningham; Lujia Chen (Ocean Engineering, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Assessing structural resilience of masonry chamber-housed substations subject to flood flow and debris impact - Wenzhu Li; Lee S. Cunningham; David M. Schultz; Sarah Mander; Chin Kim Gan; Mathaios Panteli (Innovative Infrastructure Solutions, 2025)
Chamber-housed substations are a common substation type, essential for voltage regulation, load balancing, and fault isolation to ensure power supply grid stability and reliability. As typically ground-based structures, chamber-housed substations are vulnerable to damage from flooding. In the case of chambers constructed from plain masonry, these may be susceptible to structural damage from forces generated by flood flows. Although previous studies have examined substation failures based on flood levels, they often overlook the structural damage caused by moving floodwaters and floating debris, thereby underestimating risks and overestimating substation resilience. The present study introduces an analytical framework that uses computational fluid dynamics (CFD) coupled with finite element (FE) analysis to predict flood forces and structural responses in a level of detail that would hitherto not be possible with existing design code approaches. The CFD-based modelling approach was validated against existing hydraulic experiments and subsequently applied to a case study of a typical masonry chamber-housed substation in Malaysia, a country prone to severe annual flooding. The results reveal that substation walls can withstand flood velocities up to 10 m/s without debris. However, the presence of debris leads to damage at velocities below 2 m/s, highlighting a significant reduction in resilience. Fragility and risk curves, derived from a normalised Weibull function, further reveal that ignoring debris impact underestimates forces on walls by 60% to 83%. These findings highlight the need to update design guidelines to account for debris impact and to develop suitable retrofitting strategies for existing chambers.

Population Genomics and the Environmental Drivers of Population Structure in a Cosmopolitan Marine Predator, Tursiops truncatus - Daniel M. Moore; Andre E. Moura; Ada Natoli; Elena Papale; Emily G. Cunningham; Mónica A. Silva; Tilen Genov; Stefania Gaspari; Giuseppa Buscaino; Per Berggren; Darren R. Gröcke; A. Rus Hoelzel (Molecular Ecology, 2025)
The marine environment comprises vast regions without physical barriers to movement, making the understanding of population isolation and the evolution of diversity challenging. This is especially the case for highly mobile marine species. Here we investigate populations of the common bottlenose dolphin ( Tursiops truncatus ) across the Mediterranean Sea and adjacent North Atlantic using high‐resolution genomic markers (RADseq) and stable isotope analyses to better understand the evolution of population structure in this system. High‐resolution genomic data and broad geographic sampling revealed patterns of structure not previously identified, and integration with stable isotope data suggests that prey choice varies across this region. Unexpected patterns included genetic and isotopic similarity between the North Atlantic and the region around Sicily (but not including the medially located Gulf of Cádiz and surrounding regions). The regional habitat within and beyond the Mediterranean Sea is structured with ocean frontal systems including thermal and halocline transitions, several of which show alignment with genetic transitions within our data. Our data help to distinguish among possible drivers of population differentiation for a marine predator that has the potential for long‐distance dispersion.

Increasing the spiciness of a lunch meal influences oral processing behaviors and decreases food and energy intake - Paige M. Cunningham; Isaiah M. Smith; John E. Hayes (Food Quality and Preference, 2025)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

A Review of Methionine and Cysteine: Their Roles as Sinks for Reactive Oxygen and Nitrogen Species, Including Bioinformatic Analysis of Their Percent Compositions in Metabolic Proteins - Bethany F. Laatsch; Burhan A. Ali; Anna R. Berthiaume; Grace C. Cunningham; Sabrina M. Duncan; Nathan Hau; Audrey Ho; Marais A. Loomis; Harrison R. Lowater; Brenya L. McNally; Kate L. Mueller; Matt Poppitz; et al. (Indian Journal of Clinical Biochemistry, 2025)

High satiety: Evaluating determinants of energy compensation and intake in multiple preloading studies - Barbara J. Rolls; Liane S. Roe; Paige M. Cunningham; Kathleen L. Keller; Faris M. Zuraikat (Appetite, 2025)

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

The psychedelic (−)-2,5-dimethoxy-4-iodoamphetamine [(−)-DOI] demonstrates efficacy in reducing cocaine reward and motivation in male rats - Leah M. Salinsky; Christina R. Merritt; Erik J. Garcia; Robert G. Fox; Joshua C. Zamora; Noelle C. Anastasio; Kathryn A. Cunningham (Psychopharmacology, 2025)
Rationale and objectives Overdose fatalities involving cocaine continue to rise with over 5.3 million cocaine users reported in the United States in 2022. The abuse liability of cocaine is reliant upon inhibition of dopamine ( DA ) reuptake and consequent increase in DA efflux in meso-corticolimbic circuitry that controls reward and motivation. Cocaine also increases serotonin ( 5-HT ) efflux which is integral in cocaine abuse. The 5-HT 2A receptor ( 5-HT 2A R ) is a key regulator of meso-corticolimbic DA release and controls cellular mechanisms underlying cocaine effects. 5-HT 2A R actions contribute importantly to psychedelic mechanisms of action, and the efficacy of these compounds in limiting cocaine intake is unknown. The present studies evaluated the efficacy of acute administration of a psychedelic to reduce cocaine intake using standard and advanced preclinical models of drug self-administration. Methods Both a standard fixed ratio ( FR ) schedule and behavioral economics threshold procedure of cocaine intravenous self-administration were employed to evaluate the efficacy of the psychedelic 5-HT 2A R agonist (−)-2,5-dimethoxy-4-iodoamphetamine [ ( − )-DOI ] to decrease cocaine intake and motivation for cocaine in male rats. The 5-HT 2A R-selective antagonist M100907 was utilized to explore the role of 5-HT 2A R in the effects of (−)-DOI on cocaine intake. Results We found that (−)-DOI dose-dependently reduced intake on the FR5 schedule of cocaine IVSA and left shifted the demand curve to evoke greater sensitivity to price increases in the behavioral economics paradigm. Pretreatment with M100907 abated the efficacy of (−)-DOI on cocaine intake in both paradigms. Conclusion (−)-DOI ‘devalued’ cocaine reward and motivation to take cocaine in a 5-HT 2A R-dependent manner. As serotonergic psychedelics emerge as therapeutic candidates, investigations of 5-HT 2A R-acting psychedelics in preclinical analyses of cocaine intake and relapse vulnerability during abstinence will be valuable as prelude to future clinical trials.

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Long-term trajectories of impacts and recovery of headwater stream temperatures after forest harvest in interior British Columbia - Douglas C. Braun; Dylan S. Cunningham; Herb E. Herunter; Sean M. Naman; Amanda M. Martens (Forest Ecology and Management, 2025)

Lifecycle implications and mechanical properties of carbonated biomass ashes as carbon-storing supplementary cementitious materials - Patrick R. Cunningham; Li Wang; Seth Kane; Alyson Kim; Bryan M. Jenkins; Sabbie A. Miller (Biomass and Bioenergy, 2025)

Escalating threats: house mouse attacks on adult wandering albatrosses spread across Marion Island - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Rhiannon Gill; Vanessa Stephen; Susan J. Cunningham; Peter G. Ryan (Biological Invasions, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Accumulation of benzotriazole UV-stabilizers in relation to ingested plastics and associated health metrics in Larus gulls feeding at a landfill in Atlantic Canada - Kerry Schutten; André Morrill; Zhe Lu; Akshaya Chandrashekar; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire M. Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Navigating the risks and rewards of scavenging in multipredator, human‐impacted landscapes - Calum X. Cunningham; Rebecca Windell; Lauren C. Satterfield; Aaron J. Wirsing; Thomas M. Newsome; Taylor R. Ganz; Laura R. Prugh (Ecology, 2025)
Large carnivores can influence smaller scavengers through both positive and negative interactions (e.g., carrion provisioning and intraguild killing) and ultimately shape scavenging efficiency. However, we know little about this trade‐off in anthropogenic landscapes where humans kill carnivores and provide carrion subsidies. In the context of wolf ( Canis lupus ) recolonization of human‐impacted landscapes in Washington, USA, we investigated how sources of ungulate mortality (wolves, cougars [ Puma concolor ], and vehicles) shape scavenging efficiency, community‐wide carcass visitations, and the strategies used by scavengers to navigate risk–reward trade‐offs. Cougar and wolf kills mostly occurred in areas with low‐to‐moderate human influence, whereas roadkill typically occurred in areas with high human impact. Wolves consumed their kills most rapidly (median Cathartes aura ) and black bears ( Ursus americanus ), which are obligate and apex scavengers, respectively, coincided with a seasonal increase in scavenging by most other species. The two mammalian mesocarnivores exhibited divergent strategies: Coyotes ( Canis latrans ) frequently scavenged but usually for short durations and with heightened vigilance at predator kills, whereas bobcats ( Lynx rufus ) visited carcasses less frequently but fed for longer durations and displayed low vigilance while scavenging. These results suggest a hierarchical decision‐making process whereby scavengers first choose whether to forage at a carcass before fine‐tuning foraging duration, using temporal refugia, or increasing vigilance. Predator recovery in human‐dominated landscapes therefore adds complexity to the spatiotemporal landscape of risks and rewards, and outcomes for scavengers will likely depend on their propensity to scavenge and vulnerability to humans and large predators.

Food switching at a meal is positively associated with change in adiposity among children at high-familial risk for obesity - Nicholas V. Neuwald; Alaina L. Pearce; Paige M. Cunningham; Marissa N. Setzenfand; Lauren Koczwara; Barbara J. Rolls; Kathleen L. Keller (Appetite, 2025)

Dip increases eating rate and promotes greater intake even when energy density is reduced - Madeline M. Harper; Paige M. Cunningham; John E. Hayes (Food Quality and Preference, 2025)

Compressive strength and regional supply implications of rice straw and rice hull ashes used as supplementary cementitious materials - Patrick R. Cunningham; Li Wang; Somayeh Nassiri; Peter Thy; John T. Harvey; Bryan M. Jenkins; Sabbie A. Miller (Resources, Conservation and Recycling, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

A Conceptual Framework for Measuring Ecological Novelty - Timothy L. Staples; Jessica Blois; Katie L. Cramer; Emer T. Cunningham; Maria Dornelas; Simon G. Haberle; Tina Heger; Wolfgang Kiessling; Anne E. Magurran; Aaron O'Dea; Amelia M. Penny; Volker C. Radeloff; et al. (Global Ecology and Biogeography, 2025)
Background Human pressures are driving the emergence of unprecedented, ‘novel’, ecological and environmental systems. The concept of novel (eco)systems is well accepted by the scientific community, but the use and measurement of novelty has outgrown initial definitions and critiques. There are still unresolved methodological and conceptual differences in quantifying novelty that prevent a unified research approach. Framework Here we present a conceptual framework and guidelines to unify past and future measurement of ecological novelty. Under this framework, novelty is a property of an ecological or environmental entity of interest. Novelty is quantified as the comparison between the target entity and a reference set, measured as the summary of degrees of difference across one or more dimensions. Choices in these components, particularly the reference set, can change resulting novelty measurements and inferences. Showcase We provide a case‐study to showcase our framework, measuring pre‐ and post‐European novelty in 99 pollen assemblages in Midwest USA forests. We paired this quantitative exploration with a five‐step process designed to improve the utility and outcomes of novelty analyses. Conclusions Quantitative novelty has immense value in studies of abrupt ecological change, linking climatic and ecological change, biotic interactions and invasions, species range shifts and fundamental theories. Our framework offers a unified overview and is also primed for integration into management and restoration workflows, providing consistent and robust measurements of novelty to support decision making, priority setting and resource allocation.

An interdisciplinary approach to improving conservation outcomes for parasites - Timothy M. Brown; Alison M. Dunn; Rupert J. Quinnell; Ellen Clarke; Andrew A. Cunningham; Simon J. Goodman (Conservation Biology, 2025)
Parasites represent a significant proportion of Earth's biodiversity and play important roles in the ecology and biology of ecosystems and hosts, making them an important target for conservation. Despite increasing calls to prioritize protection for parasites in the academic literature, they remain undervalued and underrepresented in global biodiversity conservation efforts, not least due to the perception that the interests of parasite and host conservation are opposing and the common misconception that parasites are a threat, rather than a benefit, to conservation. We considered whether taking an interdisciplinary approach to parasite conservation research will generate novel insights and solutions concerning why and how parasite conservation should be practiced for the benefit of parasites, their hosts, ecosystems, and people. We argue that 2 of the main barriers to more widespread parasite conservation are the knowledge gap concerning the role of sociocultural factors affecting the willingness to enact parasite conservation and the lack of a consistent and cohesive philosophical basis for parasite conservation. Possible sociocultural barriers to parasite conservation include misconceptions of the risks posed by parasites, taxonomic bias, differences in conservation values, economic constraints, and technical challenges. The use of social science can generate insights into levels of awareness and support for parasite conservation and improve understanding of how human values and attitudes mediate conservation practices concerning parasites. Such knowledge will have a critical role in addressing sociocultural barriers and improving support for parasite conservation. Issues with the current philosophical basis for parasite conservation include contradictory accounts of which parasites merit conservation, insufficient explanation of how different conservation values apply to parasite biodiversity, and the existence of a false antagonism between host and parasite conservation. Greater engagement with philosophical work on environmental ethics and biological unitization will strengthen existing arguments for parasite conservation and will support conservation decision‐making processes.

Establishing the limitations on using archived marine mammal samples for stable isotope analysis: an examination of differing preservation methods on tissues of harbor porpoise ( Phocoena phocoena ) and gray seal ( Halichoerus grypus ) - Daniel M. Moore; Emily G. Cunningham; Kayla D. Crowder; Darren R. Gröcke (Marine Mammal Science, 2025)
The use of biological samples from museum and/or archive collections is common in stable isotope research, particularly for marine mammals. Yet, the temporal stability of isotopic values across various tissue types and the influence of different preservatives on these values are not fully understood, posing significant challenges for accurate data interpretation. Here we examine the impact of three different tissue preservation methods (DMSO, ethanol, freezing), on seven different tissues (blubber, heart, kidney, lung, liver, muscle, and skin) from both a harbor porpoise ( Phocoena phocoena ) and a gray seal ( Halichoerus grypus ) for stable isotope analysis in a 1‐year period. Our results demonstrate that storage in DMSO generates greater temporal variability in δ 13 C and δ 15 N for all tissue types, particularly in the first six months of storage. Furthermore, tissues stored in DMSO often exhibited lower δ13C and δ15N values compared to those stored frozen or in ethanol. This finding highlights a significant issue for studies utilizing tissues stored in DMSO, regardless of the storage duration. These results underscore the critical need for careful consideration of preservation methods in studies involving stored tissues, providing valuable insights for experimental design and management of tissue archives.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Formation of vertical columnar seismic structures and seafloor depressions by groundwater discharge in the drowned Miami Terrace platform and overlying deep-water carbonates, southeastern Florida - Kevin J. Cunningham; Richard L. Westcott; Sean Norgard; Edward Robinson; Harry J. Dowsett; Marci M. Robinson (Marine Geology, 2024)

Advancing investigations into the effects of sweet and bitter tastes on agreeableness and hostility - Rachel S. Herz; Caitlin M. Cunningham; Theresa L. White (Food Quality and Preference, 2024)

Serving a dip with a salty snack promotes energy intake - Madeline M. Harper; Paige M. Cunningham; John E. Hayes (Food Quality and Preference, 2024)

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Body size and early marine conditions drive changes in Chinook salmon productivity across northern latitude ecosystems - Megan L. Feddern; Rebecca Shaftel; Erik R. Schoen; Curry J. Cunningham; Brendan M. Connors; Benjamin A. Staton; Al von Finster; Zachary Liller; Vanessa R. von Biela; Katherine G. Howard (Global Change Biology, 2024)
Disentangling the influences of climate change from other stressors affecting the population dynamics of aquatic species is particularly pressing for northern latitude ecosystems, where climate‐driven warming is occurring faster than the global average. Chinook salmon ( Oncorhynchus tshawytscha ) in the Yukon‐Kuskokwim (YK) region occupy the northern extent of their species' range and are experiencing prolonged declines in abundance resulting in fisheries closures and impacts to the well‐being of Indigenous people and local communities. These declines have been associated with physical (e.g., temperature, streamflow) and biological (e.g., body size, competition) conditions, but uncertainty remains about the relative influence of these drivers on productivity across populations and how salmon–environment relationships vary across watersheds. To fill these knowledge gaps, we estimated the effects of marine and freshwater environmental indicators, body size, and indices of competition, on the productivity (adult returns‐per‐spawner) of 26 Chinook salmon populations in the YK region using a Bayesian hierarchical stock‐recruitment model. Across most populations, productivity declined with smaller spawner body size and sea surface temperatures that were colder in the winter and warmer in the summer during the first year at sea. Decreased productivity was also associated with above average fall maximum daily streamflow, increased sea ice cover prior to juvenile outmigration, and abundance of marine competitors, but the strength of these effects varied among populations. Maximum daily stream temperature during spawning migration had a nonlinear relationship with productivity, with reduced productivity in years when temperatures exceeded thresholds in main stem rivers. These results demonstrate for the first time that well‐documented declines in body size of YK Chinook salmon were associated with declining population productivity, while taking climate into account.

An economic indicator of the orbital debris environment - Nodir Adilov; Peter J. Alexander; Vitali Braun; Brendan M. Cunningham (Journal of Space Safety Engineering, 2024)

Pollination deficit in apples increases with elevation - Ann M. Fraser; Ginger R.H. Allington; Aman Luthra; Preeti Virkar; Shweta Rana; Renu Suyal; Ankita Rawat; Anmol Ratna; Kiran Cunningham; Narendra Raikwal; Anvita Pandey; Vishal Singh (Agriculture, Ecosystems & Environment, 2024)

Temporal dynamics of Devonian reef communities: Insights into natural phase shifts and long-term resilience in the face of environmental variability - Amanda Godbold; Nina Clark; Emer T. Cunningham; David J. Bottjer; John M. Pandolfi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Intensive professional vehicle-based shooting provides local control of invasive rusa deer in a peri-urban landscape - Sebastien Comte; Andrew J. Bengsen; Calum X. Cunningham; Michelle Dawson; Anthony R. Pople; David M. Forsyth (Biological Invasions, 2024)
Non-native deer are becoming increasingly common in peri-urban landscapes, where they pose a risk to the health and wellbeing of people. Professional vehicle-based shooting is commonly used to control deer populations in these complex landscapes, but the effectiveness and cost of this method have seldom been evaluated. We analyzed the effectiveness and cost of using professional vehicle-based shooting to reduce the abundance and impacts of non-native rusa deer ( Cervus timorensis ) in a peri-urban landscape in Wollongong, eastern Australia, during 2011–2021. We incorporated the results from an independent monitoring program into a Bayesian joint-likelihood framework to model spatio-temporal changes in rusa deer abundance. Finally, we used our findings to assess the effect of the management program on the number of complaints from the residents. After eleven years and the removal of 4701 rusa deer from Wollongong LGA (712 km 2 ), deer abundance did not change in 74.7% of the area, decreased in 19.4% of the area (mostly in and around the sites where the professional shooting occurred), and increased in 5.9% of the area. Shooting was most cost-effective during winter when the longer hours of darkness meant that shooters could visit more sites. In contrast to deer abundance, the probability of residents complaining about deer increased in space and time. Our study shows that professional vehicle-based shooting can locally reduce the abundance of invasive deer in a peri-urban landscape, providing that sufficient control effort is expended. We suggest that shooting effort is currently too thinly spread across this peri-urban landscape, and that concentrating shooting effort on the areas of greatest deer abundance and resident complaints might be a more cost-effective strategy for managing invasive deer in peri-urban landscapes.

Unit size influences ad libitum intake in a snacking context via eating rate - Madeline M. Harper; Paige M. Cunningham; Ciarán G. Forde; John E. Hayes (Appetite, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Sources of Li isotope bias during SIMS analysis of standard glasses - Adam C. Denny; Mindy M. Zimmer; Heather S. Cunningham; Natalie E. Sievers (Chemical Geology, 2024)

Pacific salmon in the Canadian Arctic highlight a range‐expansion pathway for sub‐Arctic fishes - Karen M. Dunmall; Joseph A. Langan; Curry J. Cunningham; James D. Reist; Humfrey Melling (Global Change Biology, 2024)
Rapid climate change is altering Arctic ecosystems at unprecedented rates. These changes in the physical environment may open new corridors for species range expansions, with substantial implications for subsistence‐dependent communities and sensitive ecosystems. Over the past 20 years, rising incidental harvest of Pacific salmon by subsistence fishers has been monitored across a widening range spanning multiple land claim jurisdictions in Arctic Canada. In this study, we connect Indigenous and scientific knowledges to explore potential oceanographic mechanisms facilitating this ongoing northward expansion of Pacific salmon into the western Canadian Arctic. A regression analysis was used to reveal and characterize a two‐part mechanism related to thermal and sea‐ice conditions in the Chukchi and Beaufort seas that explains nearly all of the variation in the relative abundance of salmon observed within this region. The results indicate that warmer late‐spring temperatures in a Chukchi Sea watch‐zone and persistent, suitable summer thermal conditions in a Beaufort Sea watch‐zone together create a range‐expansion corridor and are associated with higher salmon occurrences in subsistence harvests. Furthermore, there is a body of knowledge to suggest that these conditions, and consequently the presence and abundance of Pacific salmon, will become more persistent in the coming decades. Our collaborative approach positions us to document, explore, and explain mechanisms driving changes in fish biodiversity that have the potential to, or are already affecting, Indigenous rights‐holders in a rapidly warming Arctic.

BASIS: BioAnalysis SEDFIT integrated software for cGMP analysis of SV-AUC data - Alexander E. Yarawsky; Erik S. Gough; Valeria Zai-Rose; Natalya I. Figueroa; Hazel M. Cunningham; John W. Burgner; Michael T. DeLion; Lake N. Paul (European Biophysics Journal, 2024)

Poorer inhibitory control was related to greater food intake across meals varying in portion size: A randomized crossover trial - Paige M. Cunningham; Liane S. Roe; Alaina L. Pearce; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2024)

Reasons for meal termination, eating frequency, and typical meal context differ between persons with and without a spinal cord injury - Gary J. Farkas; Paige M. Cunningham; Alicia M. Sneij; John E. Hayes; Mark S. Nash; Arthur S. Berg; David R. Gater; Barbara J. Rolls (Appetite, 2024)

Pyrogeography in flux: Reorganization of Australian fire regimes in a hotter world - Calum X. Cunningham; Grant J. Williamson; Rachael H. Nolan; Lina Teckentrup; Matthias M. Boer; David M. J. S. Bowman (Global Change Biology, 2024)
Changes to the spatiotemporal patterns of wildfire are having profound implications for ecosystems and society globally, but we have limited understanding of the extent to which fire regimes will reorganize in a warming world. While predicting regime shifts remains challenging because of complex climate–vegetation–fire feedbacks, understanding the climate niches of fire regimes provides a simple way to identify locations most at risk of regime change. Using globally available satellite datasets, we constructed 14 metrics describing the spatiotemporal dimensions of fire and then delineated Australia's pyroregions—the geographic area encapsulating a broad fire regime. Cluster analysis revealed 18 pyroregions, notably including the (1) high‐intensity, infrequent fires of the temperate forests, (2) high‐frequency, smaller fires of the tropical savanna, and (3) low‐intensity, diurnal, human‐engineered fires of the agricultural zones. To inform the risk of regime shifts, we identified locations where the climate under three CMIP6 scenarios is projected to shift (i) beyond each pyroregion's historical climate niche, and (ii) into climate space that is novel to the Australian continent. Under middle‐of‐the‐road climate projections (SSP2‐4.5), an average of 65% of the extent of the pyroregions occurred beyond their historical climate niches by 2081–2100. Further, 52% of pyroregion extents, on average, were projected to occur in climate space without present‐day analogues on the Australian continent, implying high risk of shifting to states that also lack present‐day counterparts. Pyroregions in tropical and hot‐arid climates were most at risk of shifting into both locally and continentally novel climate space because (i) their niches are narrower than southern temperate pyroregions, and (ii) their already‐hot climates lead to earlier departure from present‐day climate space. Such a shift implies widespread risk of regime shifts and the emergence of no‐analogue fire regimes. Our approach can be applied to other regions to assess vulnerability to rapid fire regime change.

First report of Ornithogalum virus 3 in Galtonia candicans in the United Kingdom - J Dixon; K Chisnall; M Mynett; C Cunningham; G Webster; A Skelton; A. R. Fowkes; A Fox (Journal of Plant Pathology, 2023)

Variety and portion size combine to increase food intake at single-course and multi-course meals - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

A co-design method for including stakeholder perspectives in nature-based flood risk management - Jill H. Slinger; Scott C. Cunningham; Baukje L. M. Kothuis (Natural Hazards, 2023)
Intervention methods to establish commitment to (collaborative) action are of potential interest to researchers and policymakers intent upon including stakeholder perspectives in natural risk governance (Scolobig, Nat Hazards 81:27–43, 2016). In this paper, a 6-step co-design method for engaging with local people in collaboratively envisioning nature-based solutions for flood defence is described. The problem structuring base of the participatory method is extended to accommodate the multi-actor situation and the local context of flood risk management. The intervention method is applied in a workshop in the Houston–Galveston Bay area in October 2014. At that time there was strong contestation surrounding the proposed Ike Dike with alternative combinations of nature-based and smaller conventional engineering solutions being proposed. The results indicate that the local participants were able to envision a wide range of future outcomes for the bay and were able to use the insights on nature-based solutions and the social contacts that they acquired at the transdisciplinary workshop to mobilize commitment to joint action. This action focused on collaboration rather than specifying ecological or technical infrastructural requirements and was instrumental in initiating more open discourse on flood defence options for the Houston–Galveston Bay area. The paper concludes that the generic applicability of the co-design method is limited by the requirement to understand and accommodate local circumstances and participants’ insights within the workshop.

Introducing the Ecosystem and Socioeconomic Profile, a Proving Ground for Next Generation Stock Assessments - S. K. Shotwell; K. Blackhart; C. Cunningham; E. Fedewa; D. Hanselman; K. Aydin; M. Doyle; B. Fissel; P. Lynch; O. Ormseth; P. Spencer; S. Zador (Coastal Management, 2023)

Occurrence and sources of microplastics on Arctic beaches: Svalbard - Tesni Lloyd-Jones; Jonathan J. Dick; Timothy P. Lane; Eoghan M. Cunningham; Konstadinos Kiriakoulakis (Marine Pollution Bulletin, 2023)

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

A zero-dose vulnerability index for equity assessment and spatial prioritization in low- and middle-income countries - C.E. Utazi; H.M.T. Chan; I. Olowe; A. Wigley; N. Tejedor-Garavito; A. Cunningham; M. Bondarenko; J. Lorin; D. Boyda; D. Hogan; A.J. Tatem (Spatial Statistics, 2023)

Intersex manifestation in the rainbow darter (Etheostoma caeruleum): Are adult male fish susceptible to developing and recovering from intersex after exposure to endocrine active compounds? - Keegan A. Hicks; Meghan L.M. Fuzzen; Hadi A. Dhiyebi; Leslie M. Bragg; Patricija Marjan; Jessie Cunningham; Mark E. McMaster; Nivetha Srikanthan; Kirsten E. Nikel; Maricor J. Arlos; Mark R. Servos (Aquatic Toxicology, 2023)

AAV analysis by sedimentation velocity analytical ultracentrifugation: beyond empty and full capsids - Alexander E. Yarawsky; Valeria Zai-Rose; Hazel M. Cunningham; John W. Burgner; Michael T. DeLion; Lake N. Paul (European Biophysics Journal, 2023)

Water motion as a conditioning mechanism to improve the yield of the sugar kelp Saccharina latissima (Phaeophyceae) - Louise Kregting; Emma Healey; Molly Crowe; Eoghan M. Cunningham (Algal Research, 2023)

The role of Dnmt1 in oocyte development - Emily A. Shelby; Elizabeth C. McKinney; Christopher B. Cunningham; Alvin M. Simmons; Allen J. Moore; Patricia J. Moore (Journal of Insect Physiology, 2023)

Switching between bites of food and sips of water is related to food intake across meals varying in portion size - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Research needs, environmental concerns, and logistical considerations for incorporating livestock grazing into coastal upland habitat management - K. Gill; K.A. Chenier; A. Free; J. Goff; J.L. Pitchford; K. Cressman; M. Posten; E. Brunden; M. Shelton; K. Swanson; S.R. Cunningham; J. Garland; et al. (Journal of Environmental Management, 2023)

Controls on the stratigraphic distribution of organic carbon in ancient deep-marine levees - Celeste M. Cunningham; Simona F. Ruso; R. William C. Arnott (Marine and Petroleum Geology, 2023)

Wild fish responses to wastewater treatment plant upgrades in the Grand River, Ontario - Kirsten E. Nikel; Gerald R. Tetreault; Patricija Marjan; Keegan A. Hicks; Meghan L.M. Fuzzen; Nivetha Srikanthan; Emily K. McCann; Hadi Dhiyebi; Leslie M. Bragg; Pam Law; Dominika Celmer-Repin; Sonya Kleywegt; et al. (Aquatic Toxicology, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Eating rate and bite size were related to food intake across meals varying in portion size: A randomized crossover trial in adults - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Anouk E.M. Hendriks-Hartensveld; Barbara J. Rolls (Appetite, 2023)

Does microplastic exposure and sex influence shell selection and motivation in the common European hermit crab, Pagurus bernhardus? - Alix McDaid; Eoghan M. Cunningham; Andrew Crump; Gary Hardiman; Gareth Arnott (Science of The Total Environment, 2023)

The transport and fate of microplastic fibres in the Antarctic: The role of multiple global processes - Eoghan M. Cunningham; Nuria Rico Seijo; Katye E. Altieri; Riesna R. Audh; Jessica M. Burger; Thomas G. Bornman; Sarah Fawcett; Claire M. B. Gwinnett; Amy O. Osborne; Lucy C. Woodall (Frontiers in Marine Science, 2022)
Understanding the transport and accumulation of microplastics is useful to determine the relative risk they pose to global biodiversity. The exact contribution of microplastic sources is hard to elucidate; therefore, investigating the Antarctic Weddell Sea, an area known for its remoteness and little human presence (i.e. limited pollution sources), will help us to better understand microplastic transportation. Here, we investigate the presence of microplastics in a range of Antarctic sample media including air, seawater, and sediment. We hypothesised that multiple transportation processes including atmospheric and oceanic vectors determine the presence of microplastics in the Antarctic. Using techniques including Polarised Light Microscopy and Raman Spectrometry, we identified mostly fibres and categorised them based on their optical and chemical properties. A total of 47 individual microplastic categories (45 of which were fibres) were identified in the air, seawater, and sediment samples. The majority of categories did not overlap multiple media (42/47); however, four fibre categories were present in both air and water samples, and another fibre category was found in all three media (category 27). We suggest that the large variety of fibres identified and the overlap of fibre categories among media indicates that the pollution may result from multiple diffuse sources and transportation pathways. Additionally, our Air Mass Back Trajectory analyses demonstrates that microplastic fibres are being transported by air masses or wind, and strongly suggests that they are transported to the Antarctic from southern South America. We also propose that fibres may be transported into the Antarctic in subsurface waters, and as pollution was identified in our sediment and additional sea ice samples, we suggest that the coastal and Antarctic deep sea may be a sink for microplastic fibres. The results shown here from a remote, near-pristine system, further highlight the need for a global response to the plastic pollution crisis.

Correction to: Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)

Starch Products as Candidate Excipients in a Continuous Direct Compression Line - Sonia M. Razavi; Yi Tao; James Scicolone; Tami Morker; Charles Cunningham; Ali Rajabi-Siahboomi; Douglas B. Hausner; Fernando J. Muzzio (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Drivers and physical processes of drought events over the State of São Paulo, Brazil - Abayomi A. Abatan; Simon F. B. Tett; Buwen Dong; Christopher Cunningham; Conrado M. Rudorff; Nicholas P. Klingaman; Rafael C. de Abreu (Climate Dynamics, 2022)
The State of São Paulo, Brazil (SSP) was impacted by severe water shortages during the intense austral summer drought of 2013/2014 and 2014/2015 (1415SD). This study seeks to understand the features and physical processes associated with these summer droughts in the context of other droughts over the region during 1961–2010. Thus, this study examines the spatio-temporal characteristics of anomalously low precipitation over SSP and the associated large-scale dynamics at seasonal timescales, using an observation-based dataset from the Climatic Research Unit (CRU) and model simulation outputs from the Met Office Hadley Centre Global Environment Model (HadGEM3-GA6 at N216 resolution). The study analyzes Historical and Natural simulations from the model to examine the role of human-induced climate forcing on droughts over SSP. Composites of large-scale fields associated with droughts are derived from ERA-20C and ERA-Interim reanalysis and the model simulations. HadGEM3-GA6 simulations capture the observed interannual variability of normalized precipitation anomalies over SSP, but with biases. Drought events over SSP are related to subsidence over the region. This is associated with reduced atmospheric moisture over the region as indicated by the analysis of the vertically integrated moisture flux convergence, which is dominated by reduced moisture flux convergence. The Historical simulations simulate the subsidence associated with droughts, but there are magnitude and location biases. The similarities between the circulation features of the severe 1415SD and other drought events over the region show that understanding of the dynamics of the past drought events over SSP could guide assessment of changes in risk of future droughts and improvements of model performance. The study highlights the merits and limitations of the HadGEM3-GA6 simulations. The model possesses the skills in simulating the large-scale atmospheric circulations modulating precipitation variability, leading to drought conditions over SSP.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Multi-taxa spatial conservation planning reveals similar priorities between taxa and improved protected area representation with climate change - Rob Critchlow; Charles A. Cunningham; Humphrey Q. P. Crick; Nicholas A. Macgregor; Michael D. Morecroft; James W. Pearce-Higgins; Tom H. Oliver; Matthew J. Carroll; Colin M. Beale (Biodiversity and Conservation, 2022)
Protected area (PA) networks have in the past been constructed to include all major habitats, but have often been developed through consideration of only a few indicator taxa or across restricted areas, and rarely account for global climate change. Systematic conservation planning (SCP) aims to improve the efficiency of biodiversity conservation, particularly when addressing internationally agreed protection targets. We apply SCP in Great Britain (GB) using the widest taxonomic coverage to date (4,447 species), compare spatial prioritisation results across 18 taxa and use projected future (2080) distributions to assess the potential impact of climate change on PA network effectiveness. Priority conservation areas were similar among multiple taxa, despite considerable differences in spatial species richness patterns; thus systematic prioritisations based on indicator taxa for which data are widely available are still useful for conservation planning. We found that increasing the number of protected hectads by 2% (to reach the 2020 17% Aichi target) could have a disproportionate positive effect on species protected, with an increase of up to 17% for some taxa. The PA network in GB currently under-represents priority species but, if the potential future distributions under climate change are realised, the proportion of species distributions protected by the current PA network may increase, because many PAs are in northern and higher altitude areas. Optimal locations for new PAs are particularly concentrated in southern and upland areas of GB. This application of SCP shows how a small addition to an existing PA network could have disproportionate benefits for species conservation.

Historical reconstruction and social context of recreational fisheries: The Australian East Coast Barramundi - Carolina Chong‐Montenegro; Ruth H. Thurstan; Alexander B. Campbell; Emer T. Cunningham; John M. Pandolfi (Fisheries Management and Ecology, 2022)
Recreational fishing in Australia makes important contributions to local economies and fisheries harvests. Historical evaluations of the cumulative effects of exploitation for most recreationally targeted Australian fish stocks remain unexplored, as do the social and cultural contexts of recreational fishing. Historical newspaper articles were used to derive quantitative and qualitative catch data on Queensland's east coast barramundi, Lates calcarifer (Bloch), a popular species targeted by recreational fishers. Decadal‐scale catch rates (1869–1952) were reconstructed, as was the development of the fishery since its earliest documentation. Models indicated a significant decline in catch rates, from an average of 5.20 kg /fishing trip (95% confidence interval, 3.82–7.09) in 1870–3.24 kg/fishing trip (95% CI 2.72–3.87) in 1952. Variability in catch rates was associated with a spatial and seasonal interaction effect, with average catch rates differing among regions and seasons. Qualitative analysis showed a northward expansion of the fishery along the east coast, coinciding with increasing number of locations fished, establishment of organised fishing clubs in the 1900s and concerns of overexploitation starting in 1909. Integration of quantitative and qualitative analysis revealed past socio‐cultural factors and trends in the barramundi fishery, while building confidence in the reliability of inferences made from archival data sets.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Role of air–sea fluxes and ocean surface density in the production of deep waters in the eastern subpolar gyre of the North Atlantic - Tillys Petit; M. Susan Lozier; Simon A. Josey; Stuart A. Cunningham (Ocean Science, 2021)
Wintertime convection in the North Atlantic Ocean is a key component of the global climate as it produces dense waters at high latitudes that flow equatorward as part of the Atlantic Meridional Overturning Circulation (AMOC). Recent work has highlighted the dominant role of the Irminger and Iceland basins in the production of North Atlantic Deep Water. Dense water formation in these basins is mainly explained by buoyancy forcing that transforms surface waters to the deep waters of the AMOC lower limb. Air–sea fluxes and the ocean surface density field are both key determinants of the buoyancy-driven transformation. We analyze these contributions to the transformation in order to better understand the connection between atmospheric forcing and the densification of surface water. More precisely, we study the impact of air–sea fluxes and the ocean surface density field on the transformation of subpolar mode water (SPMW) in the Iceland Basin, a water mass that “pre-conditions” dense water formation downstream. Analyses using 40 years of observations (1980–2019) reveal that the variance in SPMW transformation is mainly influenced by the variance in density at the ocean surface. This surface density is set by a combination of advection, wind-driven upwelling and surface fluxes. Our study shows that the latter explains ∼ 30 % of the variance in outcrop area as expressed by the surface area between the outcropped SPMW isopycnals. The key role of the surface density in SPMW transformation partly explains the unusually large SPMW transformation in winter 2014–2015 over the Iceland Basin.

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

A novel knockout mouse for the small EDRK-rich factor 2 (Serf2) showing developmental and other deficits - Karen Cleverley; Weaverly Colleen Lee; Paige Mumford; Toby Collins; Matthew Rickman; Thomas J. Cunningham; James Cleak; Joffrey Mianne; Zsombor Szoke-Kovacs; Michelle Stewart; Lydia Teboul; Cheryl Maduro; et al. (Mammalian Genome, 2021)
The small EDRK-rich factor 2 (SERF2) is a highly conserved protein that modifies amyloid fibre assembly in vitro and promotes protein misfolding. However, the role of SERF2 in regulating age-related proteotoxicity remains largely unexplored due to a lack of in vivo models. Here, we report the generation of Serf2 knockout mice using an ES cell targeting approach, with Serf2 knockout alleles being bred onto different defined genetic backgrounds. We highlight phenotyping data from heterozygous Serf2 +/− mice, including unexpected male-specific phenotypes in startle response and pre-pulse inhibition. We report embryonic lethality in Serf2 −/− null animals when bred onto a C57BL/6 N background. However, homozygous null animals were viable on a mixed genetic background and, remarkably, developed without obvious abnormalities. The Serf2 knockout mice provide a powerful tool to further investigate the role of SERF2 protein in previously unexplored pathophysiological pathways in the context of a whole organism.

GIS-based assessment of groundwater quality for drinking and irrigation purposes in central Iraq - Zaid F. Makki; Ali Adel Zuhaira; Sama M. Al-Jubouri; Rwayda Kh. S. Al-Hamd; Lee S. Cunningham (Environmental Monitoring and Assessment, 2021)

Morphine and ethanol pretreatment effects on expression and extinction of ethanol-induced conditioned place preference and aversion in mice - Christopher L. Cunningham; Lee Bakner; Lindsey M. Schuette; Emily A. Young (Psychopharmacology, 2021)

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Degrees of change: between and within population variation in thermal reaction norms of phenology in a viviparous lizard - George D. Cunningham; Geoffrey M. While; Mats Olsson; Gabriella Ljungström; Erik Wapstra (Ecology, 2020)
As the earth warms, populations will be faced with novel environments to which they may not be adapted. In the short term, populations can be buffered against the negative effects, or maximize the beneficial effects, of such environmental change via phenotypic plasticity and, in the longer term, via adaptive evolution. However, the extent and direction of these population‐level responses will be dependent on the degree to which responses vary among the individuals within them (i.e., within population variation in plasticity), which is, itself, likely to vary among populations. Despite this, we have estimates of among‐individual variation in plastic responses across multiple populations for only a few systems. This lack of data limits our ability to predict the consequences of environmental change for population and species persistence accurately. Here, we utilized a 16‐yr data set from climatically distinct populations of the viviparous skink Niveoscincus ocellatus tracking over 1,200 litters from more than 600 females from each population to examine inter‐ and intrapopulation variability in the response of parturition date to environmental temperature. We found that these populations share a common population‐mean reaction norm but differ in the degree to which reaction norms vary among individuals. These results suggest that even where populations share a common mean‐level response, we cannot assume that they will be affected similarly by altered environmental conditions. If we are to assess how changing climates will impact species and populations accurately, we require estimates of how plastic responses vary both among and within populations.

Genetic assignment, diversity, and divergence of naturalised Acacia saligna (Fabaceae) in Tigray, Ethiopia - M. A. Millar; K. Mezgebe; N. Hagazi; P. Cunningham; M. Byrne (Tree Genetics & Genomes, 2020)

Stroke Induces Prolonged Changes in Lipid Metabolism, the Liver and Body Composition in Mice - Michael J. Haley; Claire S. White; Daisy Roberts; Kelly O’Toole; Catriona J. Cunningham; Jack Rivers-Auty; Conor O’Boyle; Conor Lane; Oliver Heaney; Stuart M. Allan; Catherine B. Lawrence (Translational Stroke Research, 2020)
During recovery, stroke patients are at risk of developing long-term complications that impact quality of life, including changes in body weight and composition, depression and anxiety, as well as an increased risk of subsequent vascular events. The aetiologies and time-course of these post-stroke complications have not been extensively studied and are poorly understood. Therefore, we assessed long-term changes in body composition, metabolic markers and behaviour after middle cerebral artery occlusion in mice. These outcomes were also studied in the context of obesity, a common stroke co-morbidity proposed to protect against post-stroke weight loss in patients. We found that stroke induced long-term changes in body composition, characterised by a sustained loss of fat mass with a recovery of lean weight loss. These global changes in response to stroke were accompanied by an altered lipid profile (increased plasma free fatty acids and triglycerides) and increased adipokine release at 60 days. After stroke, the liver also showed histological changes indicative of liver damage and a decrease in plasma alanine aminotransferase (ALT) was observed. Stroke induced depression and anxiety-like behaviours in mice, illustrated by deficits in exploration, nest building and burrowing behaviours. When initial infarct volumes were matched between mice with and without comorbid obesity, these outcomes were not drastically altered. Overall, we found that stroke induced long-term changes in depressive/anxiety-like behaviours, and changes in plasma lipids, adipokines and the liver that may impact negatively on future vascular health.

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Yeasts Influence Host Selection and Larval Fitness in Two Frugivorous Carpophilus Beetle Species - Farrukh Baig; Kevin Farnier; Alexander M. Piper; Robert Speight; John Paul Cunningham (Journal of Chemical Ecology, 2020)

Floral resources of an invasive shrub alter native bee communities at different vertical strata in forest-edge habitat - M. J. Cunningham-Minnick; T. O. Crist (Biological Invasions, 2020)

Driven by speculation, not by impact – the effects of plastic on fish species - Eoghan M. Cunningham; Konstadinos Kiriakoulakis; Jaimie T. A. Dick; Louise Kregting; Pia Schuchert; Julia D. Sigwart (Journal of Fish Biology, 2020)

High temperatures are associated with substantial reductions in breeding success and offspring quality in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. Er; S. J. Cunningham (Oecologia, 2020)

Residual vitellus and energetic state of wolf spiderlings Pardosa saltans after emergence from egg-sac until first predation - A. Laino; M. Cunningham; F. Garcia; M. Trabalon (Journal of Comparative Physiology B, 2020)

Better off dead: assessment of aquatic disinfectants and thermal shock treatments to prevent the spread of invasive freshwater bivalves - Neil E. Coughlan; Stephanie J. Bradbeer; Ross N. Cuthbert; Eoghan M. Cunningham; Kate Crane; Stephen Potts; Joe M. Caffrey; Frances E. Lucy; Alison M. Dunn; Eithne Davis; Trevor Renals; Claire Quinn; et al. (Wetlands Ecology and Management, 2020)
Biosecurity protocols designed to prevent further spread of invasive alien species have become a key component of invader management strategies. Yet, the species-specific efficacy of many biosecurity treatments are frequently unclear or unknown. Invasive quagga, Dreissena bugensis , and zebra mussels, D. polymorpha , are a serious threat to freshwater ecosystems worldwide. Here, we examine the effectiveness of immersion (≤ 90 min) within 2% or 4% solutions for two commonly used disinfectants (Virasure® Aquatic and Virkon® Aquatic) to cause mortality of adult Dreissena bivalves . Further, we assessed the effectiveness of thermal treatments: steam spray (≥ 100 °C; ≤ 120 s); hot air (− 500 °C; ≤ 60 s); and dry ice exposure (− 78 °C; ≤ 300 g; 15 min). Complete mortality of D. polymorpha was observed following exposure to both disinfectants for 90 min, at both concentrations. However, high but incomplete mortality (40–90%) was recorded for D. bugensis across disinfectant treatments. For both species, complete mortality was achieved following 30 s of steam. In addition, 10 s of hot air and 15 min exposure to 300 g of dry ice can both completely killed groups of D. polymorpha . Overall, although the disinfectants did not cause complete mortality, it appears that relatively brief exposure to thermal treatments could be used to curtail the further spread of Dreissena species.

Inferring seasonal infection risk at population and regional scales from serology samples - Mark Q. Wilber; Colleen T. Webb; Fred L. Cunningham; Kerri Pedersen; Xiu‐Feng Wan; Kim M. Pepin (Ecology, 2020)
Accurate estimates of seasonal infection risk can be used by animal health officials to predict future disease risk and improve understanding of the mechanisms driving disease dynamics. It can be difficult to estimate seasonal infection risk in wildlife disease systems because surveillance assays typically target antibodies (serosurveillance), which are not necessarily indicative of current infection, and serosurveillance sampling is often opportunistic. Recently developed methods estimate past time of infection from serosurveillance data using quantitative serological assays that indicate the amount of antibodies in a serology sample. However, current methods do not account for common opportunistic and uneven sampling associated with serosurveillance data. We extended the framework of survival analysis to improve estimates of seasonal infection risk from serosurveillance data across population and regional scales. We found that accounting for the right‐censored nature of quantitative serology samples greatly improved estimates of seasonal infection risk, even when sampling was uneven in time. Survival analysis can also be used to account for common challenges when estimating infection risk from serology data, such as biases induced by host demography and continually elevated antibodies following infection. The framework developed herein is widely applicable for estimating seasonal infection risk from serosurveillance data in humans, wildlife, and livestock.

Juggling a “junk-food” diet: responses of an urban bird to fluctuating anthropogenic-food availability - M. Stofberg; S.J. Cunningham; P. Sumasgutner; A. Amar (Urban Ecosystems, 2019)

Mutations in sorghum SBEIIb and SSIIa affect alkali spreading value, starch composition, thermal properties and flour viscosity - Stefanie Griebel; Richard P. Westerman; Adedayo Adeyanju; Charles Addo-Quaye; Bruce A. Craig; Clifford F. Weil; Suzanne M. Cunningham; Bhavesh Patel; Osvaldo H. Campanella; Mitchell R. Tuinstra (Theoretical and Applied Genetics, 2019)
Key message Seven novel alleles of SBEIIb and one allele of SSIIa co-segregated with the ASV phenotype and contributed to distinct starch quality traits important for food-processing applications. Abstract Sorghum is an important food crop for millions of people in Africa and Asia. Whole-genome re-sequencing of sorghum EMS mutants exhibiting an alkali spreading value (ASV) phenotype revealed candidate SNPs in Sobic.004G163700 and Sobic.010G093400 . Comparative genomics identified Sobic.010G093400 as a starch synthase IIa and Sobic.004G163700 as a starch branching enzyme IIb . Segregation analyses showed that mutations in Sobic.010G093400 or Sobic.004G163700 co-segregated with the ASV phenotype. Mutants in SSIIa exhibited no change in amylose content but expressed lower final viscosity and lower starch gelatinization temperature (GT) than starches from non-mutant plants. The sbeIIb mutants exhibited significantly higher amylose levels and starch GT and lower viscosity compared to non-mutant starches and ssIIa mutants. Mutations in SBEIIb had a dosage-dependent effect on amylose content. Double mutants of sbeIIb and ssIIa resembled their sbeIIb parent in amylose content, starch thermal properties and viscosity profiles. These variants will provide opportunities to produce sorghum varieties with modified starch end-use qualities important for the beer brewing and baking industries and specialty foods for humans with diabetes.

The costs of keeping cool: behavioural trade-offs between foraging and thermoregulation are associated with significant mass losses in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. J. Cunningham (Oecologia, 2019)

Uses for humanised mouse models in precision medicine for neurodegenerative disease - Remya R. Nair; Silvia Corrochano; Samanta Gasco; Charlotte Tibbit; David Thompson; Cheryl Maduro; Zeinab Ali; Pietro Fratta; Abraham Acevedo Arozena; Thomas J. Cunningham; Elizabeth M. C. Fisher (Mammalian Genome, 2019)
Neurodegenerative disease encompasses a wide range of disorders afflicting the central and peripheral nervous systems and is a major unmet biomedical need of our time. There are very limited treatments, and no cures, for most of these diseases, including Alzheimer’s Disease, Parkinson's Disease, Huntington Disease, and Motor Neuron Diseases. Mouse and other animal models provide hope by analysing them to understand pathogenic mechanisms, to identify drug targets, and to develop gene therapies and stem cell therapies. However, despite many decades of research, virtually no new treatments have reached the clinic. Increasingly, it is apparent that human heterogeneity within clinically defined neurodegenerative disorders, and between patients with the same genetic mutations, significantly impacts disease presentation and, potentially, therapeutic efficacy. Therefore, stratifying patients according to genetics, lifestyle, disease presentation, ethnicity, and other parameters may hold the key to bringing effective therapies from the bench to the clinic. Here, we discuss genetic and cellular humanised mouse models, and how they help in defining the genetic and environmental parameters associated with neurodegenerative disease, and so help in developing effective precision medicine strategies for future healthcare.

Vitellogenesis in spiders: first analysis of protein changes in different reproductive stages of Polybetes pythagoricus - S. Romero; A. Laino; F. Arrighetti; C. F. García; M. Cunningham (Journal of Comparative Physiology B, 2019)

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Modeling the Effect of TNF-α upon Drug-Induced Toxicity in Human, Tissue-Engineered Myobundles - Brittany N. J. Davis; Jeffrey W. Santoso; Michaela J. Walker; Catherine E. Oliver; Michael M. Cunningham; Christian A. Boehm; Danielle Dawes; Samantha L. Lasater; Kim Huffman; William E. Kraus; George A. Truskey (Annals of Biomedical Engineering, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Arctic Mediterranean exchanges: a consistent volume budget and trends in transports from two decades of observations - Svein Østerhus; Rebecca Woodgate; Héðinn Valdimarsson; Bill Turrell; Laura de Steur; Detlef Quadfasel; Steffen M. Olsen; Martin Moritz; Craig M. Lee; Karin Margretha H. Larsen; Steingrímur Jónsson; Clare Johnson; et al. (Ocean Science, 2019)
The Arctic Mediterranean (AM) is the collective name for the Arctic Ocean, the Nordic Seas, and their adjacent shelf seas. Water enters into this region through the Bering Strait (Pacific inflow) and through the passages across the Greenland–Scotland Ridge (Atlantic inflow) and is modified within the AM. The modified waters leave the AM in several flow branches which are grouped into two different categories: (1) overflow of dense water through the deep passages across the Greenland–Scotland Ridge, and (2) outflow of light water – here termed surface outflow – on both sides of Greenland. These exchanges transport heat and salt into and out of the AM and are important for conditions in the AM. They are also part of the global ocean circulation and climate system. Attempts to quantify the transports by various methods have been made for many years, but only recently the observational coverage has become sufficiently complete to allow an integrated assessment of the AM exchanges based solely on observations. In this study, we focus on the transport of water and have collected data on volume transport for as many AM-exchange branches as possible between 1993 and 2015. The total AM import (oceanic inflows plus freshwater) is found to be 9.1 Sv (sverdrup, 1 Sv =106 m3 s−1) with an estimated uncertainty of 0.7 Sv and has the amplitude of the seasonal variation close to 1 Sv and maximum import in October. Roughly one-third of the imported water leaves the AM as surface outflow with the remaining two-thirds leaving as overflow. The overflow water is mainly produced from modified Atlantic inflow and around 70 % of the total Atlantic inflow is converted into overflow, indicating a strong coupling between these two exchanges. The surface outflow is fed from the Pacific inflow and freshwater (runoff and precipitation), but is still approximately two-thirds of modified Atlantic water. For the inflow branches and the two main overflow branches (Denmark Strait and Faroe Bank Channel), systematic monitoring of volume transport has been established since the mid-1990s, and this enables us to estimate trends for the AM exchanges as a whole. At the 95 % confidence level, only the inflow of Pacific water through the Bering Strait showed a statistically significant trend, which was positive. Both the total AM inflow and the combined transport of the two main overflow branches also showed trends consistent with strengthening, but they were not statistically significant. They do suggest, however, that any significant weakening of these flows during the last two decades is unlikely and the overall message is that the AM exchanges remained remarkably stable in the period from the mid-1990s to the mid-2010s. The overflows are the densest source water for the deep limb of the North Atlantic part of the meridional overturning circulation (AMOC), and this conclusion argues that the reported weakening of the AMOC was not due to overflow weakening or reduced overturning in the AM. Although the combined data set has made it possible to establish a consistent budget for the AM exchanges, the observational coverage for some of the branches is limited, which introduces considerable uncertainty. This lack of coverage is especially extreme for the surface outflow through the Denmark Strait, the overflow across the Iceland–Faroe Ridge, and the inflow over the Scottish shelf. We recommend that more effort is put into observing these flows as well as maintaining the monitoring systems established for the other exchange branches.

Pharmaceutical Development of AAV-Based Gene Therapy Products for the Eye - Gerard A. Rodrigues; Evgenyi Shalaev; Thomas K. Karami; James Cunningham; Nigel K. H. Slater; Hongwen M. Rivers (Pharmaceutical Research, 2019)
A resurgence of interest and investment in the field of gene therapy, driven in large part by advances in viral vector technology, has recently culminated in United States Food and Drug Administration approval of the first gene therapy product targeting a disease caused by mutations in a single gene. This product, LUXTURNA™ (voretigene neparvovec-rzyl; Spark Therapeutics, Inc., Philadelphia, PA), delivers a normal copy of the RPE65 gene to retinal cells for the treatment of biallelic RPE65 mutation–associated retinal dystrophy, a blinding disease. Many additional gene therapy programs targeting both inherited retinal diseases and other ocular diseases are in development, owing to an improved understanding of the genetic basis of ocular disease and the unique properties of the ocular compartment that make it amenable to local gene therapy. Here we review the growing body of literature that describes both the design and development of ocular gene therapy products, with a particular emphasis on target and vector selection, and chemistry, manufacturing, and controls.

Topical Drug Delivery to the Posterior Segment of the Eye: Addressing the Challenge of Preclinical to Clinical Translation - Gerard A. Rodrigues; David Lutz; Jie Shen; Xiaoda Yuan; Hong Shen; James Cunningham; Hongwen M. Rivers (Pharmaceutical Research, 2018)

Thioredoxin overexpression in both the cytosol and mitochondria accelerates age-related disease and shortens lifespan in male C57BL/6 mice - Geneva M. Cunningham; Lisa C. Flores; Madeline G. Roman; Christie Cheng; Sara Dube; Colton Allen; Joseph M. Valentine; Gene B. Hubbard; Yidong Bai; Thomas L. Saunders; Yuji Ikeno (GeroScience, 2018)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

The accessibility and utilization of genetic testing for inherited heart rhythm disorders: a Canadian cross-sectional survey study - Thomas M. Roston; Laura Dewar; Sonia Franciosi; Julie Hathaway; Kirsten Bartels; Taylor Cunningham; Karen A. Gibbs; Sam Sheps; Zachary W. M. Laksman; Shubhayan Sanatani; Andrew D. Krahn (Journal of Community Genetics, 2018)

Embryonic and post-embryonic development inside wolf spiders’ egg sac with special emphasis on the vitellus - M. Trabalon; F. Ruhland; A. Laino; M. Cunningham; F. Garcia (Journal of Comparative Physiology B, 2018)

Frequency, duration and severity of drought in the Semiarid Northeast Brazil region - S. S. B. Brito; A. P. M. A. Cunha; C. C. Cunningham; R. C. Alvalá; J. A. Marengo; M. A. Carvalho (International Journal of Climatology, 2018)
Drought is the natural disaster that impacts the greatest number of people and produces the most significant economic losses. This work presents a quantitative assessment of drought events occurred in the Semiarid region of Northeast Brazil during 1981–2016. The purpose of this study is to provide an overview of drought intensity for the last 36 years, analysing their severity, frequency and duration, considering hydro‐meteorological and agricultural aspects. To evaluate these two aspects, the 12‐month standardized precipitation index and the vegetation health index were considered to investigate drought characteristics. The definition of drought event for both these indices was performed regarding start and end month. In this context, drought duration is considered equal to the number of months of event, drought frequency is the number of events per time period and the drought severity is the absolute value of integral area below zero. Results show that the most severe and prolonged drought occurred in 2011–2016. In a clear contrast to previous droughts in past decades, during these last 5‐years period drought were more frequent, severe and affected a larger area with significant impacts for population, as well as economical activities.

How Will Climate Change Affect Road Salt Export from Watersheds? - Cassandre R. Stirpe; Mary Ann Cunningham; Kirsten M. Menking (Water, Air, & Soil Pollution, 2017)

Two Gut-Associated Yeasts in a Tephritid Fruit Fly have Contrasting Effects on Adult Attraction and Larval Survival - Alexander M. Piper; Kevin Farnier; Tomas Linder; Robert Speight; John Paul Cunningham (Journal of Chemical Ecology, 2017)

The effect of motor overflow on bimanual asymmetric force coordination - David A. Cunningham; Sarah M. Roelle; Didier Allexandre; Kelsey A. Potter-Baker; Vishwanath Sankarasubramanian; Jayme S. Knutson; Guang H. Yue; Andre G. Machado; Ela B. Plow (Experimental Brain Research, 2017)

Effects of past and present livestock grazing on herpetofauna in a landscape‐scale experiment - Geoffrey M. Kay; Alessio Mortelliti; Ayesha Tulloch; Philip Barton; Daniel Florance; Saul A. Cunningham; David B. Lindenmayer (Conservation Biology, 2017)
Livestock grazing is the most widespread land use on Earth and can have negative effects on biodiversity. Yet, many of the mechanisms by which grazing leads to changes in biodiversity remain unresolved. One reason is that conventional grazing studies often target broad treatments rather than specific parameters of grazing (e.g., intensity, duration, and frequency) or fail to account for historical grazing effects. We conducted a landscape‐scale replicated grazing experiment (15,000 km 2 , 97 sites) to examine the impact of past grazing management and current grazing regimes (intensity, duration, and frequency) on a community of ground‐dwelling herpetofauna (39 species). We analyzed community variables (species richness and composition) for all species and built multiseason patch‐occupancy models to predict local colonization and extinction for the 7 most abundant species. Past grazing practices did not influence community richness but did affect community composition and patch colonization and extinction for 4 of 7 species. Present grazing parameters did not influence community richness or composition, but 6 of the 7 target species were affected by at least one grazing parameter. Grazing frequency had the most consistent influence, positively affecting 3 of 7 species (increased colonization or decreased extinction). Past grazing practice affected community composition and population dynamics in some species in different ways, which suggests that conservation planners should examine the different grazing histories of an area. Species responded differently to specific current grazing practices; thus, incentive programs that apply a diversity of approaches rather than focusing on a change such as reduced grazing intensity should be considered. Based on our findings, we suggest that determining fine‐scale grazing attributes is essential for advancing grazing as a conservation strategy.

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Interaction rewiring and the rapid turnover of plant–pollinator networks - Paul J. CaraDonna; William K. Petry; Ross M. Brennan; James L. Cunningham; Judith L. Bronstein; Nickolas M. Waser; Nathan J. Sanders (Ecology Letters, 2017)
Whether species interactions are static or change over time has wide‐reaching ecological and evolutionary consequences. However, species interaction networks are typically constructed from temporally aggregated interaction data, thereby implicitly assuming that interactions are fixed. This approach has advanced our understanding of communities, but it obscures the timescale at which interactions form (or dissolve) and the drivers and consequences of such dynamics. We address this knowledge gap by quantifying the within‐season turnover of plant–pollinator interactions from weekly censuses across 3 years in a subalpine ecosystem. Week‐to‐week turnover of interactions (1) was high, (2) followed a consistent seasonal progression in all years of study and (3) was dominated by interaction rewiring (the reassembly of interactions among species). Simulation models revealed that species’ phenologies and relative abundances constrained both total interaction turnover and rewiring. Our findings reveal the diversity of species interactions that may be missed when the temporal dynamics of networks are ignored.

Clinostomum album n. sp. and Clinostomum marginatum (Rudolphi, 1819), parasites of the great egret Ardea alba L. from Mississippi, USA - Thomas G. Rosser; Neely R. Alberson; Ethan T. Woodyard; Fred L. Cunningham; Linda M. Pote; Matt J. Griffin (Systematic Parasitology, 2017)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

The Severity of Gliosis in Hippocampal Sclerosis Correlates with Pre-Operative Seizure Burden and Outcome After Temporal Lobectomy - Alexandra M. Johnson; Ella Sugo; Daniela Barreto; Chee-Chung Hiew; John A. Lawson; Anne M. Connolly; Ernest Somerville; Enisa Hasic; Annie ME Bye; Anne M Cunningham (Molecular Neurobiology, 2016)

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation - James R. Butler; Gregory R. Martens; Jose L. Estrada; Luz M. Reyes; Joseph M. Ladowski; Cesare Galli; Andrea Perota; Conor M. Cunningham; Matthew Tector; A. Joseph Tector (Transgenic Research, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Ecological and socio-economic factors affecting extinction risk in parrots - George Olah; Stuart H. M. Butchart; Andy Symes; Iliana Medina Guzmán; Ross Cunningham; Donald J. Brightsmith; Robert Heinsohn (Biodiversity and Conservation, 2016)

Darting Primates in the Field: A Review of Reporting Trends and a Survey of Practices and Their Effect on the Primates Involved - Elena P. Cunningham; Steve Unwin; Joanna M. Setchell (International Journal of Primatology, 2015)

Serosurvey of canine distemper virus and canine parvovirus in wild canids and domestic dogs at the rural interface in the Coquimbo Region, Chile - G. Acosta-Jamett; A. A. Cunningham; B. M. deC. Bronsvoort; S. Cleaveland (European Journal of Wildlife Research, 2015)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

Does morphology predict trophic position and habitat use of ant species and assemblages? - H. Gibb; J. Stoklosa; D. I. Warton; A. M. Brown; N. R. Andrew; S. A. Cunningham (Oecologia, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Towards climate-resilient restoration in mesic eucalypt woodlands: characterizing topsoil biophysical condition in different degradation states - Suzanne M. Prober; Jacqui Stol; Melissa Piper; V.V.S.R. Gupta; Saul A. Cunningham (Plant and Soil, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

Effects of dopamine receptor antagonists on the acquisition of ethanol-induced conditioned place preference in mice - Melanie M. Pina; Christopher L. Cunningham (Psychopharmacology, 2014)

The interaction between a drying climate and land use affects forest structure and above‐ground carbon storage - Joanne M. Bennett; Shaun C. Cunningham; Christine A. Connelly; Rohan H. Clarke; James R. Thomson; Ralph Mac Nally (Global Ecology and Biogeography, 2013)
Aim Climate change has been linked to negative effects on vegetation, including drought‐induced dieback. Large‐scale dieback not only leads to considerable carbon emissions but often leads to loss of ecological resources. We investigated whether, and how, the structure, composition and carbon content changed over a period of extended drought (the ‘ B ig D ry’) in a much‐modified forest ecosystem. We explored whether landscape configuration, management practice or soil type influenced vegetation change. Location The B ox‐ I ronbark forests of south‐eastern A ustralia. Methods In 2010, we remeasured 120 forest transects that had first been measured in 1997 by using identical field methods. Vegetation structure and composition were quantified. We used allometric growth models to estimate the expected increase in above‐ground carbon ( AGC ) storage between 1997 and 2010; these estimates were compared with observed values. Results Forest structure was systematically different between the two periods. Canopy cover, shrub cover and litter decreased between the 1997 and 2010 surveys, whereas total basal area of dead trees, dead trees in all size classes and saplings increased between the two surveys. Climate, fragment size and their interaction were the major predictors of change in most of the measured vegetation characteristics. By comparing measured AGC in 2010 and estimates from growth models, we estimated that 5.6 ± 2.1 SE t C ha −1 may have been foregone over the B ig D ry. Main conclusions Our findings add to the evidence linking climate change to negative effects on vegetation, including mortality, canopy dieback and reduced carbon sequestration. These effects may be amplified in fragmented vegetation because of greater water and heat stress. If the carbon sequestration deficit of c. 5.6 t C ha −1 were to apply across the extant Box‐Ironbark forests of V ictoria ( c . 255,400 ha), then 1.43 M t of carbon sequestration may not have occurred during the B ig D ry.

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

The influences of climatic variation and vegetation on stream biota: lessons from the B ig D ry in southeastern A ustralia - James R. Thomson; Nick R. Bond; Shaun C. Cunningham; Leon Metzeling; Paul Reich; Ross M. Thompson; Ralph Mac Nally (Global Change Biology, 2012)
Aquatic biodiversity faces increasing threats from climate change, escalating exploitation of water and land use intensification. Loss of vegetation in catchments (= watersheds) has been identified as a substantial problem for many river basins, and there is an urgent need to better understand how climate change may interact with changes in catchment vegetation to influence the ecological condition of freshwater ecosystems. We used 20 years of biological monitoring data from V ictoria, southeastern A ustralia, to explore the influences of catchment vegetation and climate on stream macroinvertebrate assemblages. Southeastern A ustralia experienced a severe drought from 1997 to 2009, with reductions of stream flows >50% in some areas. The prolonged drying substantially altered macroinvertebrate assemblages, with reduced prevalence of many flow‐dependent taxa and increased prevalence of taxa that are tolerant of low‐flow conditions and poor water quality. Stream condition, as assessed by several commonly used macroinvertebrate indices, was consistently better in reaches with extensive native tree cover in upstream catchments. Prolonged drought apparently caused similar absolute declines in macroinvertebrate condition indices regardless of vegetation cover, but streams with intact catchment and riparian vegetation started in better condition and remained so throughout the drought. The largest positive effects of catchment tree cover on both water quality and macroinvertebrate assemblages occurred above a threshold of ca. 60% areal tree cover in upstream catchments and in higher rainfall areas. Riparian tree cover also had positive effects on macroinvertebrate assemblages, especially in warmer catchments. Our results suggest that the benefits of extensive tree cover via improved water quality and in‐channel habitat persist during drought and show the potential for vegetation management to reduce negative impacts of climatic extremes for aquatic ecosystems.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Influence of carbon sources and electron shuttles on ferric iron reduction by Cellulomonas sp. strain ES6 - Robin Gerlach; Erin K. Field; Sridhar Viamajala; Brent M. Peyton; William A. Apel; Al B. Cunningham (Biodegradation, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Involvement of the orexin/hypocretin system in ethanol conditioned place preference - Charlene M. Voorhees; Christopher L. Cunningham (Psychopharmacology, 2011)

Endotoxin-induced HIF-1α stabilisation in equine endothelial cells: synergistic action with hypoxia - A. C. Brooks; N. Menzies-Gow; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2010)

Comparison of the DNA methylation profiles of human peripheral blood cells and transformed B-lymphocytes - Yan V. Sun; Stephen T. Turner; Jennifer A. Smith; Pamela I. Hammond; Alicia Lazarus; Jodie L. Van De Rostyne; Julie M. Cunningham; Sharon L. R. Kardia (Human Genetics, 2010)

The contribution of eastern-boundary density variations to the Atlantic meridional overturning circulation at 26.5° N - M. P. Chidichimo; T. Kanzow; S. A. Cunningham; W. E. Johns; J. Marotzke (Ocean Science, 2010)
We study the contribution of eastern-boundary density variations to sub-seasonal and seasonal anomalies of the strength and vertical structure of the Atlantic Meridional Overturning Circulation (AMOC) at 26.5° N, by means of the RAPID/MOCHA mooring array between April 2004 and October 2007. The major density anomalies are found in the upper 500 m, and they are often coherent down to 1400 m. The densities have 13-day fluctuations that are apparent down to 3500 m. The two strategies for measuring eastern-boundary density – a tall offshore mooring (EB1) and an array of moorings on the continental slope (EBH) – show little correspondence in terms of amplitude, vertical structure, and frequency distribution of the resulting basin-wide integrated transport fluctuations, implying that there are significant transport contributions between EB1 and EBH. Contrary to the original planning, measurements from EB1 cannot serve as backup or replacement for EBH: density needs to be measured directly at the continental slope to compute the full-basin density gradient. Fluctuations in density at EBH generate transport variability of 2 Sv rms in the AMOC, while the overall AMOC variability is 4.8 Sv rms. There is a pronounced deep-reaching seasonal cycle in density at the eastern boundary, which is apparent between 100 m and 1400 m, with maximum positive anomalies in spring and maximum negative anomalies in autumn. These changes drive anomalous southward upper mid-ocean flow in spring, implying maximum reduction of the AMOC, and vice-versa in autumn. The amplitude of the seasonal cycle of the AMOC arising from the eastern-boundary densities is 5.2 Sv peak-to-peak, dominating the 6.7 Sv peak-to-peak seasonal cycle of the total AMOC. Our analysis suggests that the seasonal cycle in density may be forced by the strong near-coastal seasonal cycle in wind stress curl.

Clear and independent associations of several HLA-DRB1 alleles with differential antibody responses to hepatitis B vaccination in youth - Yufeng Li; Rong Ni; Wei Song; Wenshuo Shao; Sadeep Shrestha; Sushma Ahmad; Coleen K. Cunningham; Patricia M. Flynn; Bill G. Kapogiannis; Craig M. Wilson; Jianming Tang (Human Genetics, 2009)

Resource allocation in a social wasp: effects of breeding system and life cycle on reproductive decisions - ELIZABETH L. JOHNSON; TYLER W. CUNNINGHAM; SARAH M. MARRINER; JENNIFER L. KOVACS; BRENDAN G. HUNT; DIMPAL B. BHAKTA; MICHAEL A. D. GOODISMAN (Molecular Ecology, 2009)
Organisms must make important decisions on how to allocate resources to reproduction. We investigated allocation decisions in the social wasp Vespula maculifrons to understand how social insects make reproductive choices. We first determined how annual colonies apportioned resources to growth and reproduction by analysing developing brood. In contrast to expectations, colonies invested in both growth (workers) and reproduction (males) simultaneously. In addition, colonies showed evidence of producing males in pulses and reversing their reproductive choices by decreasing investment in males late in the season. This reversal is consistent with theory suggesting that colonies decrease production in males if fitness of late emerging males is low. To further investigate reproductive decisions within colonies, we determined if the male mates of multiply‐mated queens varied in their reproductive success over time. Sperm use by queens did vary over time suggesting that male success may depend on sperm clumping within the female reproductive tract. Finally, we tested if colony sex ratio conformed to expectations under kin selection theory that nestmate relatedness would positively correlate with investment in new queens if workers controlled sex allocation. Surprisingly, the proportion of queens produced by colonies was negatively correlated with nestmate relatedness, suggesting that allocation may be shaped by advantages arising from increased genetic diversity resulting from multiple mating by queens. Overall, our study suggests that the reproductive decisions of colonies are flexible and may depend both on environmental cues arising from energetic needs of the colony and genetic cues arising from mating behaviours of queens.

A Robust Technique for Mapping Vegetation Condition Across a Major River System - S. C. Cunningham; R. Mac Nally; J. Read; P. J. Baker; M. White; J. R. Thomson; P. Griffioen (Ecosystems, 2009)

A six-year study of fire-related flowering cues and coexistence of two perennial grasses in a wet longleaf pine (Pinus palustris) savanna - J. Stephen Brewer; Amy L. Cunningham; Timothy P. Moore; Randell M. Brooks; Joanne L. Waldrup (Plant Ecology, 2009)

Patterns in the distribution of myctophid fish in the northern Scotia Sea ecosystem - Martin A. Collins; Jose C. Xavier; Nadine M. Johnston; Anthony W. North; Peter Enderlein; Geraint A. Tarling; Claire M. Waluda; Elizabeth J. Hawker; Nathan J. Cunningham (Polar Biology, 2008)

Landscape effects on crop pollination services: are there general patterns? - Taylor H. Ricketts; James Regetz; Ingolf Steffan‐Dewenter; Saul A. Cunningham; Claire Kremen; Anne Bogdanski; Barbara Gemmill‐Herren; Sarah S. Greenleaf; Alexandra M. Klein; Margaret M. Mayfield; Lora A. Morandin; Alfred Ochieng’; et al. (Ecology Letters, 2008)
Pollination by bees and other animals increases the size, quality, or stability of harvests for 70% of leading global crops. Because native species pollinate many of these crops effectively, conserving habitats for wild pollinators within agricultural landscapes can help maintain pollination services. Using hierarchical Bayesian techniques, we synthesize the results of 23 studies – representing 16 crops on five continents – to estimate the general relationship between pollination services and distance from natural or semi‐natural habitats. We find strong exponential declines in both pollinator richness and native visitation rate. Visitation rate declines more steeply, dropping to half of its maximum at 0.6 km from natural habitat, compared to 1.5 km for richness. Evidence of general decline in fruit and seed set – variables that directly affect yields – is less clear. Visitation rate drops more steeply in tropical compared with temperate regions, and slightly more steeply for social compared with solitary bees. Tropical crops pollinated primarily by social bees may therefore be most susceptible to pollination failure from habitat loss. Quantifying these general relationships can help predict consequences of land use change on pollinator communities and crop productivity, and can inform landscape conservation efforts that balance the needs of native species and people.

A cDNA Microarray for Crassostrea virginica and C. gigas - Matthew J. Jenny; Robert W. Chapman; Annalaura Mancia; Yian A. Chen; David J. McKillen; Hal Trent; Paul Lang; Jean-Michel Escoubas; Evelyne Bachere; Viviane Boulo; Z. John Liu; Paul S. Gross; et al. (Marine Biotechnology, 2007)

Levels of intra-host and temporal sequence variation in a large CO1 sub-units from Anisakis simplex sensu stricto (Rudolphi 1809) (Nematoda: Anisakisdae): implications for fisheries management - M. A. Cross; C. Collins; N. Campbell; P. C. Watts; J. C. Chubb; C. O. Cunningham; E. M. C. Hatfield; K. MacKenzie (Marine Biology, 2007)

Endotoxin-induced activation of equine platelets: evidence for direct activation of p38 MAPK pathways and vasoactive mediator production - A. C. Brooks; N. J. Menzies-Gow; C. Wheeler-Jones; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2007)

Role of test activity in ethanol-induced disruption of place preference expression in mice - Christina M. Gremel; Christopher L. Cunningham (Psychopharmacology, 2007)

Nearshore fish ( Pholis gunnellus ) persists across the North Atlantic through multiple glacial episodes - M. J. HICKERSON; C. W. CUNNINGHAM (Molecular Ecology, 2006)
The intertidal biota of the North Atlantic is characterized by two disjunct communities (North American and European) exposed to different climatic regimes during the Pleistocene and in the Holocene. We collect multilocus DNA sequence data from the nearshore fish Pholis gunnellus to help uncover processes determining biogeographical persistence during periodic coastal glaciations. Coalescent‐based estimates from the multilocus DNA sequence data suggest that P. gunnellus persisted on both sides of the North Atlantic throughout the last two glacial maxima (> 202 000 years) with little trans‐Atlantic gene flow since divergence, very little structure among populations within Europe (Φ ST ST = 0.0–0.21). Although the ecological flexibility and high local migration of P. gunnellus could have enhanced this species’ survival across the Atlantic, logistic regression did not find a significant determinant of trans‐Atlantic persistence when considering 12 other North Atlantic phylogeographical studies from the literature.

New Resources for Marine Genomics: Bacterial Artificial Chromosome Libraries for the Eastern and Pacific Oysters (Crassostrea virginica and C. gigas) - Charles Cunningham; Jun-ichi Hikima; Matthew J. Jenny; Robert W. Chapman; Guang-Chen Fang; Chris Saski; Mats L. Lundqvist; Rod A. Wing; Pauline M. Cupit; Paul S. Gross; Greg W. Warr; Jeff P. Tomkins (Marine Biotechnology, 2006)

Feline Immunodeficiency Virus and Puma Lentivirus in Florida panthers (Puma concolor coryi): Epidemiology and Diagnostic Issues - D. L. Miller; S. K. Taylor; D. S. Rotstein; M. B. Pough; M. C. Barr; C. A. Baldwin; M. Cunningham; M. Roelke; D. Ingram (Veterinary Research Communications, 2006)

Characterisation of the European Marine Sites in South West England: The Fal and Helford Candidate Special Area of Conservation (cSAC) - W. J. Langston; B. S. Chesman; G. R. Burt; M. Taylor; R. Covey; N. Cunningham; P. Jonas; S. J. Hawkins (Hydrobiologia, 2006)

Equine CCL11 induces eosinophil cytoskeletal reorganization and activation - M. C. Weston; M. E. Collins; F. M. Cunningham (Inflammation Research, 2006)

Phosphate nutrition effects on growth, phosphate transporter transcript levels and physiology of alfalfa cells - S. F. Abu. Qamar; T. G. Sors; S. M. Cunningham; B. C. Joern; J. J. Volenec (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

The role of protein kinase C in regulating equine eosinophil adherence and superoxide production - M. F. Sepulveda; E. C. Greenaway; M. Avella; N. T. Goode; F. M. Cunningham (Inflammation Research, 2005)

Mitochondrial evolution and phylogeography in the hydrozoan Obelia geniculata (Cnidaria) - A. F. Govindarajan; K. M. Halanych; C. W. Cunningham (Marine Biology, 2005)

Discrepancy Between Antennal and Behavioral Responses for Enantiomers of α-Pinene: Electrophysiology and Behavior of Helicoverpa armigera (Lepidoptera) - C. D. Hull; J. P. Cunningham; C. J. Moore; M. P. Zalucki; B. W. Cribb (Journal of Chemical Ecology, 2004)

Vulnerability of mouse cortical neurons to doxorubicin-induced apoptosis is strain-dependent and is correlated with mRNAs encoding Fas, Fas-Ligand, and metalloproteinases - M. Wetzel; J. Tibbitts; G. A. Rosenberg; L. A. Cunningham (Apoptosis, 2004)

Effects of dopamine D 1 - or D 2 -like receptor antagonists on the hypermotive and discriminative stimulus effects of (+)-MDMA - Marcy J. Bubar; Kami M. Pack; Paul S. Frankel; Kathryn A. Cunningham (Psychopharmacology, 2004)

Antioxidant enzyme activity and mRNA expression in the islets of Langerhans from the BB/S rat model of type 1 diabetes and an insulin-producing cell line - Louise A. Sigfrid; James M. Cunningham; Neil Beeharry; L. A. Hkan Borg; Alma L. Rosales Hernandez; Carina Carlsson; Adrian J. Bone; Irene C. Green (Journal of Molecular Medicine, 2004)

The sodium channel blocker RS100642 reverses down-regulation of the sodium channel α-subunit Nav 1.1 expression caused by transient ischemic brain injury in rats - C. Yao; A. J. Williams; X. -C. M. Lu; R. A. Price; B. S. Cunningham; R. Berti; F. C. Tortella; J. R. Dave (Neurotoxicity Research, 2003)

Paradiplozoon homoion Bychowsky & Nagibina, 1959 versus P. gracile Reichenbach-Klinke, 1961 (Monogenea): two species or phenotypic plasticity? - I. Matejusová; B. Koubková; M. Gelnar; C.O. Cunningham (Systematic Parasitology, 2002)

Redescription of Gyrodactylus teuchis Lautraite, Blanc, Thiery, Daniel & Vigneulle, 1999 (Monogenea: Gyrodactylidae); a species identified by ribosomal RNA sequence - Carey O. Cunningham; Tor Atle Mo; Catherine M. Collins; Kurt Buchmann; Richard Thiery; Guillaume Blanc; Armand Lautraite (Systematic Parasitology, 2001)

Factors affecting the presence of the cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ) in southern Australia: integrating climatic, terrain and disturbance predictors of distribution patterns - D. B. Lindenmayer; B. G. Mackey; R. B. Cunningham; C. F. Donnelly; I. C. Mullen; M. A. McCarthy; A. M. Gill (Journal of Biogeography, 2000)
Aim This study identified the factors influencing the presence, stocking rate and basal area of the southern Australian cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ). Location This investigation was conducted in the montane ash forests of the Central Highlands of Victoria, south‐eastern Australia. Methods The occurrence of N. cunninghamii was measured as part of field surveys of 474 sites (2844 plots) distributed widely throughout mountain ash ( Eucalyptus regnans ), alpine ash ( E. delegatensis ) and shining gum ( E. nitens ) forests. Statistical analysis was employed to examine relationships between the occurrence of N. cunninghamii and measured site attributes and interpolated and derived environmental variables. Results The presence of N. cunninghamii was significantly related to five variables: the age of the overstorey eucalypt stand, dominant species of overstorey eucalypt tree, topographic position in the landscape, slope and the estimated quantity of precipitation in the warmest quarter of the year. N. cunninghamii was more likely to occur in old growth eucalypt stands, in gullies and locations with high values for rainfall in the warmest quarter. In addition, there was an interaction between slope and dominant eucalypt tree species—in forests dominated by E. regnans , N. cunninghamii was more likely to occur on steep slopes whereas in E. nitens and E. delegatensis ‐dominated stands, N. cunninghamii was more likely to occur on flatter terrain. Statistical modelling also showed a significant positive effect of slope on both the stocking rate and basal area of the species. The stocking rate of N. cunninghamii also was significantly higher in old growth eucalypt stands. Main conclusions The study demonstrated that the patterns of distribution of N. cunninghamii may be more complex than recognized previously and it illustrated the importance of multiple factors including climatic conditions, disturbance processes (as reflected through the age of the dominant overstorey eucalypt stands) and topography. Our work also shows there can be complex interactions between age cohorts of different tree species in the same stand—in this case, the dominant overstorey eucalypts and the understorey which includes N. cunninghamii stems.

Diminished energy metabolism and enhanced apoptosis in livers of B6C3F1 mice treated with the antihepatocarcinogen rotenone - C. Wang; J. Youssef; B. Saran; P.G. Rothberg; M.L. Cunningham; A. Molteni; M. Badr (Molecular and Cellular Biochemistry, 1999)

Genetic differences in cocaine-induced conditioned place preference in mice depend on conditioning trial duration - Christopher L. Cunningham; Shelly D. Dickinson; Nicholas J. Grahame; Dobrina M. Okorn; Carrie S. McMullin (Psychopharmacology, 1999)

Insulitis and mechanisms of disease resistance: studies in an animal model of insulin dependent diabetes mellitus - A. J. Bone; P. R. Hitchcock; D. J. Gwilliam; J. M. Cunningham; J. Barley (Journal of Molecular Medicine, 1999)

Extinction of ethanol-induced conditioned place preference and conditioned place aversion: effects of naloxone - Christopher L. Cunningham; Carly M. Henderson; Nancy M. Bormann (Psychopharmacology, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

The discriminative stimulus properties of cocaine: effects of microinfusion of cocaine, a 5-HT 1A agonist or antagonist, into the ventral tegmental area - R. De La Garza II; Patrick M. Callahan; K. A. Cunningham (Psychopharmacology, 1998)

Analysis of the human Sonic Hedgehog coding and promoter regions in sacral agenesis, triphalangeal thumb, and mirror polydactyly - F. R. Vargas; E. Roessler; Karin Gaudenz; E. Belloni; Alexander S. Whitehead; Peader N. Kirke; James L. Mills; George Hooper; Roger E. Stevenson; Isabel Cordeiro; Patricia Correia; Temis Felix; et al. (Human Genetics, 1998)

Comparative phylogeography and the history of endemic vertebrates in the Wet Tropics rainforests of Australia - C. J. SCHNEIDER; M. CUNNINGHAM; C. MORITZ (Molecular Ecology, 1998)
We examine the effects of historical climate change on vertebrate differentiation in tropical rainforest by comparing phylogeographic patterns in six species of widespread rainforest‐restricted herpetofauna from throughout the Wet Tropics of Australia. Qualitative and quantitative comparisons of phylogeographic structure reveal strikingly similar patterns of pre‐Pleistocene vicariant population differentiation on either side of a previously identified biogeographic break (variously referred to as the Black Mountain Barrier or Corridor; BMC). While divergence across the BMC antedates the Pleistocene, the impact of Quaternary climate change is apparent in populations on either side of the BMC. Consistent with palaeoclimatological reconstructions for the region, the distribution and degree of mtDNA diversity suggests that populations were fragmented and reduced to multiple refugia during Pleistocene glacial periods, with expansion following Holocene rainforest recovery. This pattern is repeated on both sides of the BMC, but substantial differences in the amount and distribution of mtDNA diversity within species indicate the importance of species‐specific ecological characteristics. The historical processes of extinction and (re)colonization revealed by the comparative phylogeographic analysis of mtDNA sequences substantiate earlier suggestions that current regional patterns of species distribution and diversity in the Wet Tropics are largely determined by local extinctions and subsequent recolonization driven by Quaternary climate changes.

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Portage: A new early-maturing, round white table potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1995)

Prestile: A new round white potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1994)

Factors governing the adaptation of cells in area-17 of the cat visual cortex - T. Maddess; M. E. McCourt; B. Blakeslee; R. B. Cunningham (Biological Cybernetics, 1988)

Chronic effects of ingested asbestos in rats - H. M. Cunningham; C. A. Moodie; G. A. Lawrence; R. D. Pontefract (Archives of Environmental Contamination and Toxicology, 1977)

Inheritance of resistance to Verticillium wilt in Wisconsin - D. E. Hunter; H. M. Darling; F. J. Stevenson; C. E. Cunningham (American Journal of Potato Research, 1968)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Reducing sugar content of maine-grown potatoes treated with maleic hydrazide - M. E. Highlands; J. J. Licciardello; C. E. Cunningham (American Journal of Potato Research, 1952)